The Influence of Digital Ethics on the Social Media Usage Behavior of Students - Lazzuardi Anwar Zidni; Fitria Ekarini (Lembaran Ilmu Kependidikan, 2025)
Background – The productivity of MSMEs plays a strategic role in the development of sustainable tourism villages, as strong marketing capacity determines the visibility and competitiveness of local products. Digital marketing is essential for expanding market reach and enabling MSMEs to introduce their products to a wider audience. Purpose – This study aims to analyze the implementation of a digital marketing training program to strengthen MSME capacity in tourism village development. Method/Approach – A qualitative descriptive research design was employed. Data were collected through interview guides, observation sheets, and documentation. Data validity was ensured through source and method triangulation. The Miles and Huberman interactive analysis model—data reduction, data display, and conclusion drawing—was used to analyze the findings. Findings – The study reveals that the training program was implemented through four key stages: training design, training implementation, training evaluation, and follow-up activities. Each stage included essential components of effective training and contributed to improving participants’ understanding and skills in digital marketing practices. Conclusions – The digital marketing training program was carried out in alignment with its objectives and effectively guided MSME participants. The training elements and instructional processes followed the Kemp model, demonstrating its relevance for community-based capacity building in tourism village development. Novelty/Originality/Value – This study contributes to the literature by providing a structured analysis of digital marketing training implementation within the context of tourism village development. Unlike previous studies that focus primarily on digital marketing outcomes, this research emphasizes the instructional design, stages, and practical applicability of the Kemp model in MSME capacity-building programs.